The synergistic effect of rigid and flexible substituents on insertion polymerization with α-diimine nickel and palladium catalysts. Issue 32 (9th August 2021) - Hai, Zijuan; Lu, Zhou; Li, Shuaikang; Cao, Zhong-Yan; Dai, Shengyu
Abstract : The introduction of flexible cycloalkyl groups greatly enhanced the chain growth in the Ni(ii ) catalytic system and facilitated the insertion of polar monomers in the Pd(ii ) catalytic system. Abstract : α-Diimine catalysts with rigid steric hindrance groups demonstrated great potential in the field of olefin polymerization. We have recently focused on developing bulky yet flexible alkyl-substituted α-diimine catalysts and their application in the olefin insertion polymerization. In this contribution, we described the synthesis and characterization of a series of unsymmetrical α-diimine ligands bearing flexible cycloalkyl and rigid diphenylmethyl moieties and the corresponding Ni(ii ) and Pd(ii ) complexes. The unsymmetrical Ni(ii ) complexes exhibited very high catalytic activities (up to 1.4 × 10 7 gmol −1 h −1 ) and yielded polyethylene with very high molecular weights ( M n up to 967 kg mol −1 ) and branching densities (70–92/1000 C) in the ethylene polymerization. The obtained polyethylene products were excellent thermoplastic elastomers (SR up to 83%). On the other hand, the corresponding Pd(ii ) complexes showed moderate catalytic activities and generated polyethylene with high molecular weights ( M n up to 422 kg mol −1 ) and high branching densities (64–82/1000 C). Moreover, in the ethylene/polar monomer copolymerization, the Pd(ii ) complexes demonstrated moderate catalytic activities and generated moderate-to-high molecular-weight polar functional copolymers ( M n up to 92 kg mol −1 ) with tunable incorporation ratios (up to 11.57 mol%) and high branching densities (65–85/1000 C). Compared with the rigid and bulky diphenylmethyl-substituted Ni(ii ) or Pd(ii ) catalysts, the novel catalysts bearing flexible cycloalkyl and rigid diphenylmethyl substituents showed a remarkably higher catalytic activity (up to 10 times), a higher molecular weight, a higher branching density, and a better elastic recovery under the given experimental conditions for the Ni(ii ) species and exhibited much better incorporation ratios (up to 7 times) of the polar monomer for the Pd(ii ) species. Most interestingly, the introduction of flexible cycloalkyl groups greatly enhanced the chain growth of the Ni(ii ) catalytic system and facilitated the synthesis of the high-molecular-weight polymer compared with the rigid and bulky diphenylmethyl-substituted Ni(ii ) catalyst in a short time. In addition, the size of the ligand's cycloalkyl ring and its electronic properties significantly influenced the ethylene (co)polymerization.